Cardiointervalographical assessment of the vegetovascular balance in girls engaged in fitness aerobics - Ye. S. Inozemtseva; N. I. Goudomarova; A. V. Kabachkova (Бюллетень сибирской медицины)
Computer-aided systems for analysis of the cardiac rhythm allow the objective assessment of the functional state and peculiarities of the vegetative provision of functional reserves in an organism, revealing of the states of fatigue and overtraining, objective prediction and correction of the functional readiness to competition, development of the most favorable regime of training and recovery after physical activity.